Detection of Antibiotic Residues in Edible Poultry Tissues by Thin-Layer Chromatography (TLC) in Sher-e-Bangla Nagar, Dhaka (Research in Agriculture Livestock and Fisheries, 2026)
The use of antibiotics in poultry production has become a common practice worldwide to promote growth and prevent diseases. However, indiscriminate and excessive use of these drugs often leads to residues remaining in poultry meat and eggs, posing serious public health risks such as antimicrobial resistance, allergic reactions, and disruption of gut microbiota in consumers. In Bangladesh, particularly in urban areas like Sher-e-Bangla Nagar, poultry products are a major source of animal protein, making the issue of antibiotic residues highly relevant. Lack of awareness among farmers, improper withdrawal periods, and weak regulatory enforcement further aggravate the problem. Therefore, investigating the presence of antibiotic residues in poultry and identifying possible mitigation strategies are essential steps toward ensuring food safety, protecting consumer health, and promoting sustainable poultry production. The study was undertaken to determine antibiotic residues in poultry edible tissues and to identify possible mitigation approaches. The study conducted in Sher-e-Bangla Nagar, Dhaka, Bangladesh, analyzed 144 samples (liver, kidney, breast, and thigh muscle) from nine agro-markets. The primary detection method used was Thin Layer Chromatography (TLC). The study found a 15.28% prevalence of antibiotic residues across all samples, with breast muscle at 19.44%, thigh muscle at 11.11%, liver at 16.67%, and kidney at 13.89%. The most detected antibiotics were ciprofloxacin (7.64%), followed by oxytetracycline (6.94%), levofloxacin (0.7%), and enrofloxacin, which was not detected. Mohammadpur Krishi Market had the highest residue (31.25%). The presence of antibiotic residues in poultry poses significant risks to food safety and public health. Effective monitoring, farmer awareness, and strict enforcement of withdrawal periods are essential to reduce residue levels. Adoption of good farming practices and alternative disease control measures can ensure safer poultry production and protect consumers.Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 91-102